Sensitivity of Blastocystis sp. clinical strains to new benzimidazol derivatives - Pokhil, Sergey; Martynov, Martynov; Tymchenko, Olena; Kyrychenko , Igor (Annals of Mechnikov's Institute, 2023)
Introduction. Blastocystis sp. (formerly Blastocystis hominis) is the most common protists of the intestinal tract of humans and many species of animals. Blastocystis sp. can cause various diseases of the digestive organs, which are currently combined into a separate nosology called "blastocystosis". To date, there are no international or national recommendations for the treatment of blastocystosis, including approved drugs for this purpose. Data on the clinical and parasitological effectiveness of various drugs used to treat blastocystosis are controversial. This substantiates the relevance of the search for new compounds with pronounced anti-Blastocystis activity for the development of drugs based on them for the etiotropic therapy of blastocystosis. The goal of this study was to determine the in vitro sensitivity of clinical strains of Blastocystis sp. to new derivatives of benzimidazole in comparison with metronidazole as well as to investigate the effect of the subinhibitory concentration of the most promising benzimidazole derivative on the level of parasite virulence factors (formation of amoeboid forms and production of proteases). Materials and Methods. Five cultures of Blastocystis sp. were isolated from faecal samples of patients with irritable bowel syndrome with predominant diarrhoea (IBS-D, Rome IV). Strains of Blastocystis sp. was cultured at 37 °C under anaerobic conditions in tubes with containing 5 ml of RPMI-1640 liquid nutrient medium with L-glutamine and enclosed antibiotics (ampicillin 12 mg/ml, streptomycin 4 mg/ml) and 10 % heat-inactivated serum of horse. The group of new benzimidazole derivatives (NBDs) included: tris-benzimidazole of aconitic acid (BAA), benzimidazole of histidine (BHI), benzimidazole of lipoic acid (BLA) and bis-benzimidazole of lysine succinamide (BBL). The anti-Blastocystis activity of NBDs and metronidazole (MTZ) was evaluated in the range of their concentrations from 1000 μg/ml to 1 μg/ml for four days with daily (after 24 h, 48 h, 72 h and 96 h) determination of indicators for each drug: 50 % of the minimum inhibitory concentration (MIC50) and the minimum lethal concentration (MLC). Cell count of Blastocystis sp. was performed in a hemocytometer using the trypan blue dye exclusion test. Morphological changes in Blastocystis sp. cells induced by NBDs described according to the results of their phase-contrast microscopy. The effect of subinhibitory concentrations of NBD and MTZ on the formation of amoeboid forms (РAF) of Blastocystis sp. was established by counting the specific proportion (%) of these forms among 300 parasite cells in smears of suspensions permanently stained by the modified method according to Field. The level of protease activity (РА) in Blastocystis sp. cell lysates grown both in intact RPMI medium and in the presence of subinhibitory concentrations of NPB and MTZ was determined by the method of quantitative colorimetric analysis of azocasein cleavage. Results and Discussion. Based on the results of in vitro sensitivity studies of 5 clinical strains of Blastocystis sp. to the action of 4 NBDs (BAA, BHI, BLA and BBL) and metronidazole (MTZ), it was established that the anti-Blastocystis activity of BAA, BHI, BLA and MTZ reflects a direct positive regularity in the "concentration-response" and "contact time-response". That is, as the concentration of these benzimidazole derivatives increases, as well as the time of their action on Blastocystis sp. cultures, the manifestations of growth inhibition and death of parasite cells clearly increase. Instead, it was found that the effect of different concentrations of BBL on strains of Blastocystis sp., in the context of the "concentration-response" effect, is variable - with different directions of manifestations of this effect. In the stationary growth phase of Blastocystis sp. (72-hour parasite cultures) the MIC50 value for BLA was (7.2 ± 2.6) μg/ml and was 1.5 times, 1.6 times, 21.5 times and 1.7 times lower than the level of this indicator for BAA, BHI, BBL and MTZ, respectively (p < 0.05). In addition, BLA is 4 times superior to MTZ in the effectiveness of lethal action on Blastocystis sp. cells, which confirms the actual MLC values established for these compounds: 125 μg/ml and 500 μg/ml, respectively (p < 0.05). We discovered a deep destruction of cells of Blastocystis sp., which occurs when the parasite cultures are exposed to lethal concentrations of BLA: the central body disappears in the cells, intensive formation of granules and vacuoles is observed, thinning and loss of a clear contour of the outer shell, which is finally completely destroyed, and in place of the cells the detritus of their internal contents is revealed. Unlike MTZ, subinhibitory concentrations of BLA (≤ 2μg/ml) do not stimulate the reproduction of Blastocystis sp cells. Subinhibitory concentrations of BLA, compared to MTZ, increase the virulence potential of parasites to a lesser extent by 1.6 times according to the PAF indicator (p < 0.05) with a comparable effect of both ingredients on increasing the PA index. Conclusion. The obtained results make it possible to recognize BLA as a promising compound for further research aimed at the development of a more effective means than MTZ for the treatment of blastocystosis.